PERCEPTIONS AND EDUCATIONAL NEEDS REGARDING GLOBAL HEALTH AMONG VIETNAMESE HEALTH SCIENCE STUDENTS: A QUALITATIVE STUDY (Tạp chí Y học Cộng đồng, 2026)
Introduction: In the 21st century, Global Health (GH) has transitioned from a peripheral topic to a core component of medical education. However, in developing nations like Vietnam, the integration of GH curricula remains limited, and there is a paucity of data regarding students' specific educational needs. This study explored the qualitative definitions of GH among Vietnamese health science students and their expectations for future curriculum development.Materials and Methods: A qualitative survey study utilizing open-ended questionnaires was conducted at the University of Medicine and Pharmacy at Ho Chi Minh City from June to July 2025. This article analyzes textual responses from a sample of 532 undergraduate students across six faculties. Data regarding students' definitions of GH and recommendations for education were analyzed using Inductive Content Analysis to identify significant themes.Results: The analysis identified two primary themes. First, student conceptualizations of GH were predominantly disease-centric, reflecting a pandemic legacy, although a humanistic and ethical perspective also emerged. Second, there was a strong demand for pragmatic educational transformation, with specific requests to integrate GH into Case-Based Learning and utilize social media as an educational tool.Conclusion: Vietnamese health science students possess diverse but fragmented conceptualizations of GH, often conflating the field with disease control. Consequently, there is a critical need for a practical integration model in health professions education that shifts the focus from theory to clinical application and leverages digital platforms to meet learner expectations.
Keywords: Global Health; Qualitative Research; Curriculum; Health Occupations Students; Vietnam.